Fluid memristor based on PDMS nano channel and preparation method thereof
By forming a multi-nanochannel array on the PDMS nanochannels and connecting it with the glass reservoir, ion enrichment or depletion is achieved by applying voltage from the electrode, the problems of high power consumption and poor stability of existing solid-state memristors are solved, and the problem of high power consumption and poor stability of existing solid-state memristors is realized. Low power consumption and high stability fluid memristor, suitable for neuromorphic computing applications.
Patent Information
- Application Number
- CN202411166085.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-13
AI Technical Summary
Existing electron-based solid-state memristors are difficult to rival biological neurons in terms of power dissipation and stability, and are complex in preparation and large operating voltage, resulting in performance bottlenecks in neuromorphic calculations.
Using a fluid memristor based on PDMS nanochannels, a multi-nanochannel array is formed on a PDMS substrate and a glass reservoir is connected to the glass reservoir. The electrodes apply voltage to achieve ion enrichment or depletion in the nanochannels, resulting in a memristor effect. Reduce operating voltage and improve stability.
It realizes a low-power memristor with simple preparation and good stability, has good biocompatibility and low energy consumption, is suitable for neuromorphic computing applications, and can simulate the plasticity and short-term adjustable conductivity characteristics of biological synapses.
Smart Images

Figure CN119136648A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of micro-nano electronic devices, and in particular to a fluid memristor based on a PDMS nanochannel and a preparation method thereof. Background Art
[0002] Traditional digital computers are based on the von Neumann architecture, in which logic units are physically separated from storage units, resulting in time-consuming and energy-consuming data transmission, which becomes a bottleneck for performance and power efficiency. 15 A network of neurons connected by synapses plays a key role in the flow of information. Therefore, a new computing method, neuromorphic computing, is proposed. This method uses ultra-large-scale integrated chips to simulate the neural system of the biological brain to process information. It has the characteristics of high parallelism, low power consumption, and storage-computing fusion, and can efficiently solve computing tasks including unstructured data processing.
[0003] The development of neuromorphic computing has benefited from the introduction of memristors. In 1971, Shaotang Cai predicted the existence of the fourth basic circuit element associated with charge and magnetic flux, the memristor, from the perspective of symmetry in physics. The resistance of a memristor changes with the amount of charge flowing through it. By adjusting its resistance, it is possible to achieve adjustments similar to synaptic strength, thereby simulating the plasticity of biological synapses. Its non-volatile storage characteristics enable neural networks to maintain learning outcomes when the power is off. Memristors excel in high-speed programmability, high-density integration, and fast response, providing key support for the practicality and performance of neuromorphic computing. Since HP Labs first created a memristor in 2008, the application of various solid-state memristors has promoted cutting-edge research in the field of neuromorphic computing.
[0004] At present, electronic-based solid-state memristors have realized a variety of neuromorphic functions, but their power consumption and functions are still not comparable to those of biological neurons. Ions are the main information carriers in the human brain, and their transportation is an important signal transduction pathway. Ion-based devices have the advantages of low energy consumption, good biocompatibility, and no electromagnetic interference. Through the study of ion transport behavior at the nanoscale, nanofluid systems provide a new approach for neuromorphic computing. At present, ion-based nanofluid memristors have been realized under various mechanisms, such as interface movement and concentration polarization. However, these memristors face certain challenges, such as complex preparation, poor stability, and high power consumption due to high operating voltage. Summary of the invention
[0005] The object of the present invention is to provide a fluid memristor based on a PDMS nanochannel which is simple to prepare, has good stability and low power consumption, and a preparation method thereof.
[0006] The technical solution to achieve the purpose of the present invention is: a fluid memristor based on PDMS nanochannels, comprising a PDMS substrate, a cover glass, a liquid reservoir, and electrodes, wherein the PDMS substrate has a multi-nanochannel array, the liquid reservoir on the glass is connected through a plurality of nanochannels, the electrode is placed in the liquid reservoir, and liquid is injected into the liquid reservoir;
[0007] The liquid can undergo a solid-liquid reaction with the inner wall of the nanochannel, so that the area of the nanochannel in contact with the liquid is charged, thereby having ion selectivity, and further producing an ion-selective effect on the liquid;
[0008] The electrodes are used to apply voltage to both ends of the nanochannel. Under the drive of the electric field, ions enter or leave the nanochannel, and ion enrichment or depletion is achieved in the nanochannel, so that the nanochannel conductance changes with hysteresis compared to the voltage, generating a memristor effect, and realizing a nanofluid memristor based on the PDMS nanochannel.
[0009] Furthermore, the thickness of the PDMS substrate is 3 mm; the top cover glass is soda-lime glass with a thickness of 1 mm.
[0010] Furthermore, the number of the nanochannels is 25, and the average distance between two adjacent nanochannels is 60 μm;
[0011] The geometry of a single nanochannel is asymmetric and its width is uneven, with the widths at the two ends being 150nm and 800nm respectively, the average width being 500nm, the depth being 450nm, the length being 300μm, and the cross section being V-shaped.
[0012] Furthermore, there are two liquid reservoirs in total, which are cylindrical in shape, with a diameter of 1.5 mm, a depth of 1 mm, and a spacing of 300 μm; the liquid injected into the liquid reservoirs is a KCl solution with a concentration range of 1 mM to 1 M.
[0013] Furthermore, the electrodes are platinum sheet electrodes, two in total, with a thickness of 50 μm and a width of 0.5 mm, which are respectively arranged in the two liquid storage tanks.
[0014] A method for preparing a fluid memristor based on a PDMS nanochannel comprises the following steps:
[0015] Step 1, preparing a polystyrene nanochannel template using a crack-based non-photolithography method;
[0016] Step 2, using liquid plastic Smooth-on 305 to replicate the crack pattern on the polystyrene culture dish cover to obtain a plastic nanochannel template;
[0017] Step 3, using PDMS to replicate the nanochannel pattern on the plastic template to obtain a PDMS nanochannel;
[0018] Step 4: Use laser cutting technology to make two small holes on the glass as liquid reservoirs for the device;
[0019] Step 5: encapsulate the PDMS substrate with processed nanochannels to finally obtain a fluid memristor based on PDMS nanochannels.
[0020] Further, in step 1, a crack-based non-photolithography method is used to prepare a polystyrene nanochannel template, as follows:
[0021] Step 1.1, pour 3 ml of anhydrous ethanol into a polystyrene culture dish with a diameter of 35 mm and cover the dish with a lid;
[0022] Step 1.2, place the culture dish on a heating table and heat it at 80°C. After 3 hours, a culture dish cover having an array of parallel cracks on its inner surface is obtained.
[0023] Further, in step 2, the crack pattern on the polystyrene culture dish cover is replicated using liquid plastic Smooth-on 305 to obtain a plastic nanochannel template, as follows:
[0024] Step 2.1, mix the two components A and B in the liquid plastic Smooth-on 305 in a volume ratio of 1:1, pour into the lid of the culture dish, and let it stand at room temperature for 40 minutes to allow the liquid plastic to initially harden;
[0025] Step 2.2: Use tweezers to take out the plastic template from the culture dish and heat it on a heating table at 60°C. After 1 hour, a plastic nanochannel template is obtained.
[0026] Further, in step 3, PDMS is used to replicate the nanochannel pattern on the plastic template to obtain a PDMS nanochannel, as follows:
[0027] Step 3.1, mix the liquid PDMS and curing agent in a weight ratio of 10:1 and invert it on the plastic template;
[0028] Step 3.2, place the template on the heating table and heat it to completely cure the PDMS. Set the heating temperature to 85°C and the time to 2 hours. Then use tweezers to remove the PDMS. The nanochannel on the culture dish cover is successfully replicated on the PDMS.
[0029] Further, in step 5, the glass and the PDMS substrate with nanochannels are encapsulated as follows:
[0030] Step 5.1, activating the PDMS substrate and soda-lime glass by irradiating them with ultraviolet ozone for 15 minutes;
[0031] Step 5.2: Align and seal the glass on the PDMS substrate with the nanochannel under a microscope. After bonding, the connection direction of the two small holes on the glass remains parallel to the nanochannel on the substrate surface.
[0032] Compared with the prior art, the present invention has the following significant advantages:
[0033] (1) The preparation method is simple and low-cost, and does not require complex processing technology and expensive processing equipment;
[0034] (2) The material used to prepare the nanochannel is PDMS, which is negatively charged after contact with the solution, which is a prerequisite for achieving the memristive effect, and has the advantages of biocompatibility and high transparency;
[0035] (3) The multiple nanochannels prepared give the memristor excellent stability and reduce the operating voltage, making the device power consumption very low. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Schematic diagram of the structure of the nanofluid memristor in an embodiment of the present invention.
[0037] Figure 2 It is a SEM characterization image of the PDMS nanochannel in the embodiment of the present invention.
[0038] Figure 3 4 is an IV data curve diagram of the nanofluid memristor in an embodiment of the present invention.
[0039] Figure 4 Schematic diagram of the working principle of the nanofluid memristor in an embodiment of the present invention.
[0040] Figure 5 It is a graph of IV cycle data during the operation of the nanofluid memristor in an embodiment of the present invention.
[0041] Figure 6 4 is a graph showing PPF and PPD data during operation of the nanofluid memristor in an embodiment of the present invention. DETAILED DESCRIPTION
[0042] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0043] Combination Figure 1 The present invention discloses a fluid memristor based on PDMS nanochannels, comprising a PDMS substrate, a cover glass, a liquid reservoir, and electrodes. The PDMS substrate has a multi-nanochannel array, the liquid reservoir on the glass is connected through a plurality of nanochannels, the electrode is placed in the liquid reservoir, and liquid is injected into the liquid reservoir.
[0044] As a specific example, the thickness of the PDMS substrate is 3 mm.
[0045] As a specific example, the number of the nanochannels is 25, and the average spacing between the nanochannels is about 60 μm.
[0046] As a specific example, the single nanochannel has an asymmetric geometry and uneven width, with widths of about 150nm and 800nm at both ends respectively, an average width of about 500nm, a depth of about 450nm, a length of about 300μm, and a "V" shape in cross section.
[0047] As a specific example, the top cover glass is soda lime glass with a thickness of 1 mm.
[0048] As a specific example, there are two liquid storage tanks in total, which are cylindrical in shape, with a diameter of 1.5 mm and a depth of 1 mm, and the distance between them is about 300 μm.
[0049] As a specific example, the liquid is a KCl solution with a concentration range of 1 mM-1 M.
[0050] As a specific example, the electrodes are platinum sheet electrodes, 2 in total, with a thickness of 50 μm and a width of 0.5 mm.
[0051] A method for preparing a fluid memristor based on a PDMS nanochannel comprises the following steps:
[0052] Step 1, preparing a polystyrene nanochannel template using a crack-based non-photolithography method;
[0053] Step 2, using liquid plastic Smooth-on 305 to replicate the crack pattern on the polystyrene culture dish cover to obtain a plastic nanochannel template;
[0054] Step 3, using PDMS to replicate the nanochannel pattern on the plastic template to obtain a PDMS nanochannel;
[0055] Step 4: Use laser cutting technology to make two small holes on the glass as liquid reservoirs for the device;
[0056] As a specific example, the small holes have a diameter of 1.5 mm, a height of 1 mm, and a spacing of 300 μm;
[0057] Step 5, encapsulating the PDMS substrate with processed nanochannels, and finally obtaining a fluid memristor based on PDMS nanochannels;
[0058] As a specific example, in step 1, a crack-based non-photolithography method is used to prepare a polystyrene nanochannel template, as follows:
[0059] Step 1.1, pour 3 ml of anhydrous ethanol into a polystyrene culture dish with a diameter of 35 mm and cover the dish with a lid;
[0060] Step 1.2, place the culture dish on a heating table and heat it at 80°C. After 3 hours, a culture dish cover with a parallel crack array on the inner surface can be obtained.
[0061] As a specific example, in step 2, the crack pattern on the polystyrene culture dish cover is replicated using liquid plastic Smooth-on 305 to obtain a plastic nanochannel template, as follows:
[0062] Step 2.1, mix the two components A and B in the liquid plastic Smooth-on 305 in a volume ratio of 1:1, pour into the lid of the culture dish, and let it stand at room temperature for 40 minutes to allow the liquid plastic to initially harden;
[0063] Step 2.2: Use tweezers to take out the plastic template from the culture dish and heat it on a heating table at 60°C for 1 hour to obtain a plastic nanochannel template.
[0064] As a specific example, in step 3, PDMS is used to replicate the nanochannel pattern on the plastic template to obtain the PDMS nanochannel, as follows:
[0065] Step 3.1, mix the liquid PDMS and curing agent in a weight ratio of 10:1 and invert it on the plastic template;
[0066] Step 3.2, place the template on a heating table and heat it to completely cure the PDMS. Set the heating temperature to 85°C and the time to 2 hours. Then use tweezers to remove the PDMS. At this point, the nanochannel on the culture dish cover is successfully replicated on the PDMS.
[0067] As a specific example, in step 5, the glass is encapsulated with the PDMS having nanochannels as follows:
[0068] Step 5.1, activating the PDMS substrate and soda-lime glass by irradiating them with ultraviolet ozone for 15 minutes;
[0069] Step 5.2: Align and seal the glass on the PDMS substrate with the nanochannel under a microscope. After bonding, the connection direction of the two small holes on the glass remains parallel to the nanochannel on the substrate surface.
[0070] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0071] Example
[0072] Combination Figure 1This embodiment provides a fluid memristor based on PDMS nanochannels, including a PDMS substrate, a cover glass, a liquid reservoir, and electrodes. The PDMS substrate has a multi-nanochannel array, the liquid reservoir on the glass is connected through multiple nanochannels, the electrode is placed in the liquid reservoir, and liquid is injected into the liquid reservoir.
[0073] Furthermore, the thickness of the PDMS substrate is 3 mm.
[0074] Furthermore, the number of the nanochannels is 25, and the average spacing between the nanochannels is about 60 μm.
[0075] Furthermore, the single nanochannel has an asymmetric geometry and uneven width, with widths of about 150 nm and 800 nm at both ends respectively, an average width of about 500 nm, a depth of about 450 nm, a length of about 300 μm, and a "V" shape in cross section.
[0076] Furthermore, the top cover glass is soda-lime glass with a thickness of 1 mm.
[0077] Furthermore, there are two liquid storage tanks in total, which are cylindrical in shape, with a diameter of 1.5 mm and a depth of 1 mm, and the distance between them is about 300 μm.
[0078] Furthermore, the liquid is a KCl solution with a concentration range of 1 mM-1 M.
[0079] Furthermore, the electrodes are platinum sheet electrodes, 2 in total, with a thickness of 50 μm and a width of 0.5 mm.
[0080] This embodiment also provides a method for preparing a nanofluid memristor, comprising the following steps:
[0081] Step 1: Prepare a polystyrene nanochannel template using a crack-based non-photolithography method, as follows:
[0082] Step 1.1. Pour 3 ml of anhydrous ethanol into a polystyrene culture dish with a diameter of 35 mm and cover the dish with a lid.
[0083] Step 1.2, place the culture dish on a heating table and heat it at 80°C. After 3 hours, a culture dish cover with a parallel crack array on the inner surface can be obtained;
[0084] Step 2: Use liquid plastic Smooth-on 305 to replicate the crack pattern on the polystyrene culture dish cover to obtain a plastic nanochannel template, as follows:
[0085] Step 2.1, mix the two components A and B of Smooth-on 305 in the liquid plastic in a volume ratio of 1:1, pour into the lid of the petri dish, and let it stand at room temperature for 40 minutes to allow the liquid plastic to initially harden;
[0086] Step 2.2, take out the plastic template from the culture dish with tweezers, heat it on a heating table at 60°C for 1 hour to obtain a plastic nanochannel template;
[0087] Step 3: Use PDMS to replicate the nanochannel pattern on the plastic template to obtain a PDMS nanochannel, as follows:
[0088] Step 3.1, fully mix the liquid PDMS and curing agent in a weight ratio of 10:1, and invert it on the plastic template;
[0089] Step 3.2, place the template on a heating table and heat it to completely cure the PDMS. Set the heating temperature to 85°C for 2 hours, then use tweezers to remove the PDMS. At this point, the nanochannel on the culture dish cover is successfully replicated on the PDMS.
[0090] Step 4: Use laser cutting technology to make two small holes on the glass as liquid reservoirs for the device;
[0091] Furthermore, the diameter of the small holes is 1.5 mm, the height is 1 mm, and the spacing is 300 μm;
[0092] Step 5: Encapsulate the PDMS substrate with processed nanochannels to finally obtain a fluid memristor based on PDMS nanochannels, as follows:
[0093] Step 5.1: Activate the PDMS substrate and soda-lime glass by irradiating them with UV-ozone for 15 minutes.
[0094] Step 5.2, aligning and sealing the glass on the PDMS substrate with the nanochannel under a microscope, after bonding, the connection direction of the two small holes on the glass remains parallel to the nanochannel on the surface of the substrate;
[0095] In this embodiment, there is a parallel multi-nanochannel array on the PDMS substrate, as shown in the schematic diagram. Figure 2 In a, the average spacing between channels is about 60 μm. The image of a single nanochannel under a scanning tunneling microscope is shown in Figure 2 As shown in c, the channel has an asymmetric geometry, which is mainly manifested in the uneven width. The widths at both ends are about 150nm and 800nm respectively, the average width is about 500nm, the depth is about 450nm, and the length is about 300μm.
[0096] In this embodiment, the current response of the PDMS nanochannel-based fluidic memristor in a DC scanning mode (0→5V→0→-5V→0) is as follows: Figure 3 As shown. The corresponding current-voltage (IV) curve of the device when the reservoir is filled with 1mM KCl solution shows typical bipolar memory behavior, which is characterized by self-crossing hysteresis loops. During the forward voltage scan, the conductance of the device gradually changes from low to high, and when the voltage polarity is reversed, the conductance slowly returns to the initial value. At the same time, the IV curve shows obvious ionic current rectification behavior, that is, at the same bias amplitude, the conductance at positive polarity is higher than that at negative polarity, resulting in an asymmetric current-voltage response. These results prove that the device has a memristive effect.
[0097] Combination Figure 4 The working mechanism of the fluid memristor is that the ions in the nanochannel are enriched or depleted under the combined action of the channel surface electric field and the external electric field, resulting in the device producing two states of high conductance and low conductance, as follows: PDMS undergoes a hydrolysis reaction when in contact with KCl solution, forming a negatively charged surface. This negative surface charge repels anions in the solution and attracts cations, thereby forming an electrical double layer (EDL). In an asymmetric charged nanochannel, the surface electric field has a component V in the direction of mass transfer. s , which is related to the external bias voltage V e The superposition of the phases polarizes the ion concentration distribution. e Offset V s In the specific case of , the net polarization induced by the potential is zero. Under relatively positive bias potentials, the negative surface charge and the external potential promote the migration of cations into the nanochannel, leading to ion enrichment, cf. Figure 4 In contrast, under a relatively negative bias, the external electric field leads to ion depletion in the nanochannel, ref. Figure 4 b in the figure. Therefore, the intersection of the IV hysteresis curve represents the boundary of the potential-induced ion enrichment and depletion within the nanochannel. This ion enrichment and depletion will lead to high and low conductance states, respectively, i.e., ion current rectification. The hysteresis effect is caused by the slow redistribution of ions compared to the change of the applied potential scanned at the corresponding scan rate. The redistribution of ions corresponds to the change of ion concentration within the nanochannel. Compared with the steady-state current response under the low scan rate bias, when the scan rate is fast, the ions within the nanochannel do not have enough time to redistribute accordingly. Therefore, the conductance change is minimal and the area of the hysteresis loop is reduced.
[0098] Combination Figure 5When the voltage scanning range of the PDMS nanochannel fluid memristor is 0→5V→0→-5V→0, the number of cycles is at least 60 and the fluid memristor can maintain a stable memristive effect. It can be seen that the fluid memristor has high reliability and can be reused.
[0099] The fluid memristor provided in this embodiment is used to simulate the short-term plasticity of biological synapses. Figure 6 As shown. Specifically, by applying several consecutive triangular wave pulses (±6V, 4ms) to the device, the conductance can increase or decrease within the continuous pulse signal. This behavior is similar to the short-term plasticity of biological neurons, indicating that the device can simulate basic synaptic functions: paired pulse facilitation (PPF) and paired pulse depression (PPD), proving that the nanofluid memristor has the characteristic of adjustable conductance in the short term, which is conducive to the future application and development of the device in the field of brain-like computing.
[0100] The energy consumption of the fluid memristor based on the PDMS nanochannel provided in this embodiment can be expressed by the formula: For estimation, the voltage V is 6V, the current I is 40nA, and the pulse width t p The time taken for the pulse is 4 ms and the number of parallel channels N is 25. Therefore, the energy dissipation of a single channel is about 19 pJ / pulse, which is very low for nanofluidic memristors. These results demonstrate that our nanofluidic memristors have broad potential in neuromorphic computing applications.
[0101] The above are only preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A fluid memristor based on PDMS nanochannel, characterized in that: It includes a PDMS substrate, a top cover glass, a liquid reservoir, and an electrode. The PDMS substrate has a multi-nanochannel array, the liquid reservoir on the glass is connected through a plurality of nanochannels, the electrode is placed in the liquid reservoir, and liquid is injected into the liquid reservoir; The liquid can undergo a solid-liquid reaction with the inner wall of the nanochannel, so that the area of the nanochannel in contact with the liquid is charged, thereby having ion selectivity, and further producing an ion-selective effect on the liquid; The electrodes are used to apply voltage to both ends of the nanochannel. Under the drive of the electric field, ions enter or leave the nanochannel, and ion enrichment or depletion is achieved in the nanochannel, so that the nanochannel conductance changes with hysteresis compared to the voltage, generating a memristor effect, and realizing a nanofluid memristor based on the PDMS nanochannel.
2. The fluid memristor based on PDMS nanochannel according to claim 1, characterized in that: The thickness of the PDMS substrate is 3 mm; the top cover glass is soda-lime glass with a thickness of 1 mm.
3. The fluid memristor based on PDMS nanochannel according to claim 1, characterized in that: The number of the nanochannels is 25, and the average distance between two adjacent nanochannels is 60 μm; The geometry of a single nanochannel is asymmetric and its width is uneven, with the widths at the two ends being 150nm and 800nm respectively, the average width being 500nm, the depth being 450nm, the length being 300μm, and the cross section being V-shaped.
4. The fluid memristor based on PDMS nanochannel according to claim 1, characterized in that: There are two liquid reservoirs in total, which are cylindrical in shape, with a diameter of 1.5 mm, a depth of 1 mm, and a spacing of 300 μm; the liquid injected into the liquid reservoirs is a KCl solution with a concentration range of 1 mM to 1 M.
5. The fluid memristor based on PDMS nanochannel according to claim 4, characterized in that: The electrodes are platinum sheet electrodes, 2 in total, with a thickness of 50 μm and a width of 0.5 mm, which are respectively arranged in the two liquid storage tanks.
6. A method for preparing a fluid memristor based on PDMS nanochannel according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1, preparing a polystyrene nanochannel template using a crack-based non-photolithography method; Step 2, using liquid plastic Smooth-on 305 to replicate the crack pattern on the polystyrene culture dish cover to obtain a plastic nanochannel template; Step 3, using PDMS to replicate the nanochannel pattern on the plastic template to obtain a PDMS nanochannel; Step 4: Use laser cutting technology to make two small holes on the glass as liquid reservoirs for the device; Step 5: encapsulate the PDMS substrate with processed nanochannels to finally obtain a fluid memristor based on PDMS nanochannels.
7. The method for preparing a fluid memristor based on PDMS nanochannel according to claim 6, characterized in that: In step 1, a polystyrene nanochannel template is prepared by a crack-based non-photolithography method as follows: Step 1.1, pour 3 ml of anhydrous ethanol into a polystyrene culture dish with a diameter of 35 mm and cover the dish with a lid; Step 1.2, place the culture dish on a heating table and heat it at 80°C. After 3 hours, a culture dish cover having an array of parallel cracks on its inner surface is obtained.
8. The method for preparing a fluid memristor based on PDMS nanochannel according to claim 6, characterized in that: In step 2, the crack pattern on the polystyrene culture dish cover is replicated using liquid plastic Smooth-on 305 to obtain a plastic nanochannel template, as follows: Step 2.1, mix the two components A and B in the liquid plastic Smooth-on 305 in a volume ratio of 1:1, pour into the lid of the culture dish, and let it stand at room temperature for 40 minutes to allow the liquid plastic to initially harden; Step 2.2: Use tweezers to take out the plastic template from the culture dish and heat it on a heating table at 60°C. After 1 hour, a plastic nanochannel template is obtained.
9. The method for preparing a fluid memristor based on PDMS nanochannel according to claim 6, characterized in that: In step 3, PDMS is used to replicate the nanochannel pattern on the plastic template to obtain PDMS nanochannels, as follows: Step 3.1, fully mix the liquid PDMS and curing agent in a weight ratio of 10:1, and invert it on the plastic template; Step 3.2, place the template on the heating table and heat it to completely cure the PDMS. Set the heating temperature to 85°C and the time to 2 hours. Then use tweezers to remove the PDMS. The nanochannel on the culture dish cover is successfully replicated on the PDMS.
10. The method for preparing a fluid memristor based on PDMS nanochannel according to claim 6, characterized in that: In step 5, the glass and the PDMS substrate with nanochannels are encapsulated as follows: Step 5.1, activating the PDMS substrate and soda-lime glass by irradiating them with ultraviolet ozone for 15 minutes; Step 5.2: Align and seal the glass on the PDMS substrate with the nanochannel under a microscope. After bonding, the connection direction of the two small holes on the glass remains parallel to the nanochannel on the substrate surface.
